Analisis Teknik Penerjemahan pada Ekspresi Ketakutan Tokoh Utama dalam Novel Broken Strings - Ayuk Eka Setiani; Enggar Mulyajati (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Translating expressions of fear in literary works has its own challenges because it not only involves structural language transfer, but also maintaining emotional meaning in the text, this is the basis for this study. This study aims to identify the translation techniques used in translating the main character's expression of fear in the novel Broken Strings and the forms of linguistic expression used. The study uses a qualitative descriptive method with Molina & Albir's translation technique theory in Translation Studies as the basis for data analysis. The results of the study show that the techniques used include literal translation, reduction, and modulation. The translation techniques used in this novel are literal translation techniques (53.85%), reduction (25.00%), and modulation (21.15%). The main character's expression of fear is described through phrases and clauses in the form of psychological, metaphorical, and physical expressions, with psychological expressions being the most dominant form. This study concludes that the most dominant translation technique used is literal translation and the expression of fear is not only translated structurally, but also attempts to maintain the emotional meaning of the main character in the target language.